1991
DOI: 10.1007/bf00003583
|View full text |Cite
|
Sign up to set email alerts
|

Branch, micropropagule and tissue culture of the red algaeEucheuma denticulatum andKappaphycus alvarezii farmed in the Philippines

Abstract: Three forms of the iota-producing carrageenophyte, Eucheuma denticulatum, and four forms of the kappa-producing carrageenophyte, Kappaphycus alvarezii, obtained from seaweed farms in the Philippines have been grown in the laboratory under unialgal and axenic conditions. Comparison of media indicates that seed stocks of both species can be cultured using enriched seawater media ranging from ESS and SWMD-1 to inexpensive soil extract (Erdshreiber's) or holding in sterile seawater for up to three weeks. Microprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 15 publications
2
49
0
1
Order By: Relevance
“…Similar results were reported by Gusev et al (1987) for species of Ceramium, Laurencia, Gracilaria, Furcellaria and Phyllophora and also by Liu & Gordon (1987) for Pterocladiella capillacea. Other studies reported similar results for Porphyra umbilicalis (Liu & Kloareg, 1991), Grateloupia doryphora (Robaina et al, 1990), Eucheuma denticulatum (Dawes & Koch, 1991), Laurencia sp. (Robaina et al, 1992), Gracilaria verrucosa (Kaczyna & Megnet, 1993) and Solieria filiformis (Robledo & Garcia-Reina, 1993).…”
Section: Plant Growth Regulators (Pgr) In Rhodophytasupporting
confidence: 69%
“…Similar results were reported by Gusev et al (1987) for species of Ceramium, Laurencia, Gracilaria, Furcellaria and Phyllophora and also by Liu & Gordon (1987) for Pterocladiella capillacea. Other studies reported similar results for Porphyra umbilicalis (Liu & Kloareg, 1991), Grateloupia doryphora (Robaina et al, 1990), Eucheuma denticulatum (Dawes & Koch, 1991), Laurencia sp. (Robaina et al, 1992), Gracilaria verrucosa (Kaczyna & Megnet, 1993) and Solieria filiformis (Robledo & Garcia-Reina, 1993).…”
Section: Plant Growth Regulators (Pgr) In Rhodophytasupporting
confidence: 69%
“…According to Polne-Fuller & Gibor (1987) the development of this callus like structures both in presence and absence of plant growth regulators is due to the wound healing process in seaweeds. Plant growth regulators also promoted callus growth in Kappaphycus alvarezii (Dawes and Koch 1991;Dawes et al 1993). Sahoo and Singh (2006) studied thallus regeneration in Cystoseira indica.…”
Section: Discussionmentioning
confidence: 99%
“…Dawes and Koch (1991) and Dawes et al (1993) investigated the effect of plant growth regulators on callus development and regeneration process. Similarly, Hurtado and Cheney (2003) through tissue culture studies on Eucheuma denticulatum (Burman) Collins et Harvey generated the new strains.…”
Section: Introductionmentioning
confidence: 99%
“…Com o intuito de otimizar essa fase, alguns trabalhos foram realizados por Saga & Sakai (1983), Garcia-Reina et al (1987), Lawlor et al (1987) e Chen & McCracken (1993). Apesar dessa dificuldade, estudos sobre micropropagação, particularmente nas rodofíceas, foram realizados, mais recentemente, em vários locais do mundo, enfocando o crescimento, a indução de calos e a regeneração dos talos por Gusev et al (1987), PolneFuller & Gibor (1987), Bradley & Cheney (1991), Robaina et al (1990), Liu & Kloareg (1991), Dawes & Koch (1991), Kaczyma & Megnet (1993), Yokoya et al (1993Yokoya et al ( , 1999Yokoya et al ( , 2003, Yokoya & Handro (1996, Huang & Fujita (1997), Garcia-Jimenez et al (1998) e Yokoya (2000.…”
Section: Introductionunclassified